Variation on a theme; an overview of the Tn916/Tn1545 family of mobile genetic elements in the oral and nasopharyngeal streptococci - Santoro, Francesco; Vianna, Morgana E.; Roberts, Adam P. (Frontiers in Microbiology, 2014)
The oral and nasopharyngeal streptococci are a major part of the normal microbiota in humans. Most human associated streptococci are considered commensals however a small number of them are pathogenic, causing a wide range of diseases including oral infections such as dental caries and periodontitis and diseases at other body sites including sinusitis and endocarditis, and in the case of Streptococcus pneumoniae, meningitis. Both phenotypic and sequence based studies have shown that the human associated streptococci from the mouth and nasopharynx harbour a large number of antibiotic resistance genes and these are often located on mobile genetic elements known as conjugative transposons or integrative and conjugative elements of the Tn916 / Tn1545 family. These mobile genetic elements are responsible for the spread of the resistance genes between streptococci and also between streptococci and other bacteria. In this review we describe the resistances conferred by, and the genetic variations between the many different Tn916-like elements found in recent studies of oral and nasopharyngeal streptococci and show that Tn916-like elements are important mediators of antibiotic resistance genes within this genus. We will also discuss the role of the oral environment and how this is conducive to the transfer of these elements and discuss the contribution of both transformation and conjugation on the transfer and evolution of these elements in different streptococci.